Relationship between Thermal Stress due to Heat and the Health of the Workers of a metalworking company - Osorio Delgado, Yomayra Sandra (2024)
This article analyzes the relationship between thermal stress due to heat and the health of workers at the metalworking company in 2021.An applied approach was used, with a non-experimental cross-sectional design. The results show that 80% of male workers work more than 2 hours in conditions that include 62% of medium environmental levels and 24% of high levels of heat stress. The WBGT index in the areas of production (22.26) and accounting (17.83) does not exceed the established legal limits, but the correlation between environmental conditions and physical, mental and social health is significant, with a Spearman's Rho coefficient of 0.782 (p < 0.05). The conclusions recommend the implementation of preventive strategies such as hydration points and schedule rotation.